Effects of adults aging on word encoding in reading Chinese: evidence from disappearing text - Liu, Zhifang; Pan, Yun; Tong, Wen; Liu, Nina (PeerJ, 2017)
The effect of aging on the process of word encoding for fixated words and words presented to the right of the fixation point during the reading of sentences in Chinese was investigated with two disappearing text experiments. The results of Experiment 1 showed that only the 40-ms onset disappearance of word n disrupted young adults’ reading performance. However, for old readers, the disappearance of word n caused disruptions until the onset time was 120 ms. The results of Experiment 2 showed that the disappearance of word n + 1 did not cause disruptions to young adults, but these conditions made old readers spend more time reading a sentence compared to the normal display condition. These results indicated a reliable aging effect on the process of word encoding when reading Chinese, and that the encoding process in the preview frame was more susceptible to normal aging compared to that in the fixation frame. We propose that sensory, cognitive, and specific factors related to the Chinese language are important contributors to these age-related differences.
Keywords: Chinese reading; Words encoding; Disappearing text; Eye movements; Aging